ANALISIS PENERAPAN MANAJEMEN RISIKO KREDIT PADA PT. PEGADAIAN (PERSERO) CABANG ENREKANG - Aulia Aulia (Jurnal Ilmu Manajemen Profitability, 2019)
This study aims to determine the effectiveness of the application of credit risk management at PT. Pegadaian (Persero) Enrekang Branch. The type of research used is descriptive research with a qualitative approach by describing whether the application of credit risk management at PT. Pegadaian (Persero) Enrekang Branch has been effective.The analysis techniques used in this study are the description phase, the reduction stage and the selection stage to provide interpretation in the form of a description.The results showed that the application of credit risk management at PT.Pegadaian (Persero) Enrekang Branch ineffective because of fluctuations in bad loans from 2016 to 2018.